(untitled) (Journal of the College of Education for Women, 2019)
The Iraqi- Kuwaiti relations had witnessed a lot of problems which had its impact on them, at the fore front is the frontier issue, and the Iraqi invasion of Kuwait in 1990 which led to the severance of relations between them and had strengthened the disagreement and the dispute and raised the animosity and tension.After 2003, Iraq has witnessed a lot of changes which affected Iraq and the region as a whole.Under the new political developments in Iraq, a now phase has started in the relations between the two parts. which is based on the emphasis on building new relations based on the mutual respect and non intervention in the internal affairs of both countries, and in accordance with the principles of the international law, and which serves the mutual interests of the two countries and creat good environment for better relations.The leader of the two countries had sought to surpass the disagreements of the past, which were caused by the ill policies of the previous political system. The Kuwaiti government has helped the new political system of Iraq by giving support of the Iraqi people, and it had gaved about 1,0 billion dollar to rebuild the Iraqi infrustructure. There is also another aspect helped strengthening the relations represented by the raise in the official vistings between the leaders of the two parts that had strengthened the relations between them and surpassing the last era.